2021
DOI: 10.33448/rsd-v10i10.18609
|View full text |Cite
|
Sign up to set email alerts
|

Impacto dos sinais e sintomas de incontinência urinária na qualidade de vida de mulheres praticantes de musculação no Estado de Sergipe

Abstract: Introdução: A Incontinência Urinária (IU) é toda perda involuntária de urina, de acordo com a Sociedade Internacional de Continência (ICS). Objetivos: Analisar a prevalência de sinais e sintomas de Incontinência Urinária por esforço em mulheres praticantes de musculação. Metodologia: Estudo transversal do tipo quantitativo, realizado via online por 195 mulheres que praticavam musculação, sendo que dessas apenas 52 foram incluídas no presente estudo, as mesmas responderam a um questionário ao qual colhia inform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 12 publications
0
1
0
1
Order By: Relevance
“…According to data from the present study, most women with UI reported moderate to very severe impact. Studies such as that by Sousa et al found an impact ranging from severe to very severe in 21.15% of women in their sample, and highlight that the impact of UI is not linked solely to physical aspects, but negatively influences sexual, social, domestic and occupational aspects of women's lives 20,21 .…”
Section: Discussionmentioning
confidence: 81%
“…According to data from the present study, most women with UI reported moderate to very severe impact. Studies such as that by Sousa et al found an impact ranging from severe to very severe in 21.15% of women in their sample, and highlight that the impact of UI is not linked solely to physical aspects, but negatively influences sexual, social, domestic and occupational aspects of women's lives 20,21 .…”
Section: Discussionmentioning
confidence: 81%
“…De acordo com os dados do presente estudo, a maioria das mulheres com IU relatou impacto de moderado a muito grave. Estudos como o de Sousa et al encontraram impacto de grave a muito grave em 21,15% de mulheres da sua amostra, e destacam que o impacto da IU não está vinculado unicamente aos aspectos físicos, mas influencia de forma negativa os aspectos sexuais, sociais, domésticos e ocupacionais da vida da mulher 20,21 .…”
Section: Discussionunclassified